PreferenciasIncumbency advantage and tenure length in the chilean chamber of deputies, 1989-2009 - Bunker, Kenneth; Navia, Patricio (Revista de Ciencia Política, 2015)
This article explores incumbency advantage and tenure length in the Chilean Chamber of Deputies between 1989 and 2009. After describing how the electoral system frames electoral competition, we present descriptive data of incumbency advantage and tenure length. There is remarkable stability in both indicators. Three out of four incumbents seek re-election, 82.3% get re-elected. Still, every four years, first-termers comprise 38.5% of the 120-member Chamber. The average tenure length is 2.4 terms. We find a neutral effect of past electoral performance and number of terms in office on the decision to seek re-election and be reelected. However, the results become significant when we control for the incumbent legislators coalition.